2019
DOI: 10.1590/1983-21252019v32n327rc
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development and Tolerance of Pepper Species to Salinity Stress

Abstract: Salinity is one of the main causes of crop yield decline in arid and semi-arid regions, requiring the use of tolerant species that allow cultivation in these areas. The objective of this study was to determine the emergence, initial growth and tolerance of pepper species irrigated with saline waters. The experiment was conducted in a protected environment (greenhouse), with a 5 x 3 factorial scheme, using four replicates of 30 seeds each. The experimental design was a completely randomized design, involving fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…The reduction in dry matter (Figures 1A and B) may be related to the detrimental effects of the salt stress, since high concentrations of sodium salts negatively Table 2 -Summary of the analysis of variance for leaf dry matter (LDM), stem dry matter (STDM), root dry matter (RDM), shoot dry matter (SDM), total dry matter (TDM), and the root/shoot ratio (R/S) in soursop seedlings irrigated with saline water and submitted to different methods of hydrogen peroxide application, 145 days after sowing ns, **, * respectively, not significant, significant at p<0.01 and significant at p<0.05 affect the physiological aspects of the plant, promoting ionic, osmotic, hormonal and nutritional changes, thereby causing a reduction in growth and, consequently, in biomass accumulation (SÁ et al, 2019). In research developed by Silva et al (2019b), in soursop seedlings under salt stress (ECw ranging from 0.7 to 3.5 dS m -1 ), the authors also found a reduction in dry matter accumulation for increases in the electrical conductivity of the irrigation water.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in dry matter (Figures 1A and B) may be related to the detrimental effects of the salt stress, since high concentrations of sodium salts negatively Table 2 -Summary of the analysis of variance for leaf dry matter (LDM), stem dry matter (STDM), root dry matter (RDM), shoot dry matter (SDM), total dry matter (TDM), and the root/shoot ratio (R/S) in soursop seedlings irrigated with saline water and submitted to different methods of hydrogen peroxide application, 145 days after sowing ns, **, * respectively, not significant, significant at p<0.01 and significant at p<0.05 affect the physiological aspects of the plant, promoting ionic, osmotic, hormonal and nutritional changes, thereby causing a reduction in growth and, consequently, in biomass accumulation (SÁ et al, 2019). In research developed by Silva et al (2019b), in soursop seedlings under salt stress (ECw ranging from 0.7 to 3.5 dS m -1 ), the authors also found a reduction in dry matter accumulation for increases in the electrical conductivity of the irrigation water.…”
Section: Resultsmentioning
confidence: 99%
“…The stem dry biomass of plants irrigated with low-salinity water (S 1 ) was statistically higher than that of plants that were under irrigation with water of distinct cationic nature (Figure 3B); despite this, when analyzing only the cationic nature of the water, the effect occurred in a similar way. The reduction in biomass accumulation by passion fruit plants is also related to the osmotic effect caused by the high concentrations of salts in the root zone, promoting changes in ionic and osmotic homeostasis, thus causing a reduction in growth and, consequently, in biomass accumulation (SÁ et al, 2019). Veloso et al (2019), when evaluating the growth of 'Morada Nova' soursop plants irrigated with saline water (ECw ranging from 0.3 to 3.7 dS m -1 and with Na:Ca:Mg in the equivalent proportion of 7:2:1), also observed a reduction in the accumulation of stem dry biomass as water salinity levels increased.…”
Section: Resultsmentioning
confidence: 99%
“…The treatments were arranged in a 2 × 4 × 5 factorial scheme: two varieties of pepper (C. chinense and C. frutescens), four levels of electrical conductivity of solutions -EC (1.5, 3.0, 4.5, and 6.0dS m -1 ), and five times of seed soaking in saline solutions (2, 4, 6, 8, and 10h), totaling 120 experimental units (Table 1). The salinity level of 1.5dS m -1 was adopted as a control based on the results of a previous study (Sá et al, 2019), where the species C. chinense was considered as tolerant in its initial development up to EC of 1.55dS m -1 . Preparation of solutions and germination test.…”
Section: Methodsmentioning
confidence: 99%
“…In some regions, soil and water salinity are a growing problem for agriculture under irrigation Yuan et al, 2019;Jan et al, 2020). Information about the cultivation of pepper varieties is scarce, especially related to salt tolerance (Sá et al, 2019).…”
Section: Palabras Clavementioning
confidence: 99%